We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
343
6
avatar

Find the value of k that makes the question an identity.

k(3x-2)=4-6x

 Mar 11, 2018
 #1
avatar
0

No solution for k !!!

 Mar 11, 2018
 #2
avatar+18467 
+1

k=-2 is a solution

 Mar 11, 2018
 #3
avatar
0

How did you solve for k = -2?

 Mar 11, 2018
edited by Guest  Mar 11, 2018
 #6
avatar+18467 
+1

3kx - 2k = 4 - 6x

 

3kx = -6x      and   -2k = 4

3k = -6          and     k = -2

  k = -2

ElectricPavlov  Mar 11, 2018
 #4
avatar
+1

k(3x-2)=4-6x        divide both side by (3x - 2)

k =(4 - 6x) / (3x - 2)

k =-2(3x - 2) / (3x - 2)

k = -2

 Mar 11, 2018
edited by Guest  Mar 11, 2018
 #5
avatar+68 
+1

I'm gonna just do a different method if ya don't mind.

\(k(3x-2)=4-6x\)

\(k(3x-2)=-6x+4\)

\(k(3x-2)=-2(3x-2)\)

\(k = -2\)

.
 Mar 11, 2018

8 Online Users

avatar